Increasing the Yield of Purple Corn (Zea mays L.) through the Application of Compost Organic Fertilizer Enriched with Trichoderma - Nurnawati, Andi Ayu; Syarifuddin, Rifni Nikmat; Poleuleng, Andi Besse; Hala, Dian Magfirah (International Journal of Sustainable Applied Sciences, 2024)
Purple corn has many benefits for body health so it is necessary to develop research related to this plant. This research aims to obtain information on the effect of giving trichocompost on the production of purple corn plants as well as the recommended dosage of trichocompost fertilizer based on research results. The design method used was Randomized Block Design with treatment in the form of different doses of trichocompost fertilizer (0 tons/ha, 20 tons/ha, 25 tons/ha, 30 tons/ha, and 35 tons/ha).  Analysis of variance and the Least Significant Difference (LSD) test showed that the application of trichocompost doses had a significant effect on cob length, cob diameter, and purple corn plant yield. An application of 25 tons/ha of trichocompost can be used as the most efficient recommended dose.